Values included in Arabic language books for the fourth and fifth grades of basic education in Jordan - Alkhazaleh, Laila Hassan; Alswaid, Mohammad Khalaf (Journal of Educational and Psychological Sciences, 2020)
This study aims to explore; (The Implicated values in the Arabic language text books for the fifth and fourt grades in the elementary stage in Jordan. The researcher used the descriptive analytical descriptive method which is based on a surveying and diagilosing the educational phenomenon, revealing its aspects as well as content analysis method of the Arabic language text books to the grades of the elementary stage.As the researcher used the tool ; (questionnaire) to invistigate the degree of satisfaction of the representative sample of the Jordanian society about the favorite values ​​and the extent to which those values ​​are harmonized with the contents of the Arabic language books for the grades mentioned above. The total population of the study (13354) individuals, who are parents of students in schools in The study sample consisted of the decisions of the Arabic language text books for the basic classes from the first to the fifth, and number ten books, each class has two parts, one for the first semester, and the other for the second semester.. The researcher used in the treatment of both the statistical mean, and percentages, and duplicates, and the results were as follows: The types of the values ​​contained in the text book of the Arabic language of the first class, and how they were distributed. religious values placed ​​first, national values secondly, social values ​​thirdly, values ​​sentimental IIII, personality, cognitive, and health finally. As for the answer to the question of the appropriateness of educational values ​​contained in the Arabic language text books for grades five first mentioned from the stage of basic education for values ​​favorite among Jordanian society?: Indicate the results to that religious values ​​solved first, then the values ​​of national Secondly, then the values ​​empathy III, VI and political values finally. ​​ The researcher to discuss these results and make the necessary recommendations for researchers, teachers, and their school curricula.